Faktor Yang Mempengaruhi Petani Bawang Merah Tidak Memilih Pembiayaan Pada Bank Syariah di Nganjuk - Anantika Hanum Pratiwi; Ari Prasetyo (Universitas Airlangga, 2014)
This research purposes to determine the factors that affect onion farmers not choose financing in Sharia Banking in Nganjuk. Right now, in Sharia Banking showed rapid development but not matched by the number of customers, especially financing customers the onion farmers in Nganjuk.This research uses a quantitative approach using exploratory factor analysis. Population characteristics of this research are the onion farmers in the Ngrami village and Sukomoro Subdistrict. The number of samples during the preliminary test by conducting a written interview on 10 respondents and to the main test required 100 respondents also. The sampling technique used is purposive sampling. Results of this research showed that there are four factors affected onion farmers not to choose financing in Sharia Banking in Nganjuk. Four those factors as a result of reduction of processing factor analysis. The four factors are named with the recommendations of other factors, another competitor, locations, and popularity. Suggestion for Sharia Bank are to socialize, provide products financing in the form of seasonal for farmers, by proactive services to potential customers, and services through a car arround in a place easily accessible public. Factors that are formed in this research also can be used to further research for influence the other variables, the decision did not choose to become sharia banking customers as a whole, not only on financing customers. In addition to further research the SUbject of research is expected to wider scope. REFERENCESAnshori, Muslich dan Sri Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Pers.Antonio, Muhammad Syafi’i.2001. Bank Syariah dari Teori ke Praktek. Jakarta: Gema Insani Press.Assael, Henry. 1998.Consumer Behavior and Marketing Action. Sixth Edition. Massachussets: Kent Publishing Company. Departemen Agama RI. 2013.Al Qur’an dan Tafsirnya. Jakarta: Lentera Abadi.Effendi, Sofian. 2012. Metode Penelitian Survei. Jakarta: LP3ES.Kardes, Frank R. 2002. Consumer Behavior and Managerial Decision Making. The Second Edition. Upper Sanddle River New Jersey: Pearson Education Inc.Karim, Adiwarman dan Adi Zakaria Afif. 2008. Islamic Banking Consumer Behaviour in Indonesia: A Qualitative Approach.Kartajaya, Hermawan dan Muhammad Syakir Sula. Syariah Marketing. Bandung: PT Mizan Pustaka. Kasmir. 2004. Pemasaran Bank. Jakarta: Kencana. Kotler, Philips dan Amstrong dan Kevin Lane Keller. 2009. Manajemen Pemasaran. Edisi 13, Jilid 1. Jakarta: Erlangga.——————- dan Amstrong dan Kevin Lane Keller. 2009. Manajemen Pemasaran. Edisi 13, Jilid 2. Jakarta: ErlanggaMalhotra, Naresh K. 2010. Riset pemasaran: Pendekatan Terapan. Jilid 2. Jakarta: PT. Indeks.Muflih, Muhammad. 2006. Perilaku Konsumen Dalam Perspektif Ilmu Ekonomi Islam. Jakarta: PT RajaGrafindo Persada. Muhammad. 2005. Manajemen Pembiayaan Bank Syariah. Yogyakarta: UPP AMP YKPN. Muhammad. 2006. Bank Syariah Analisis Kekuatan, Peluang, Kelemahan dan Ancaman. Yogyakarta:Ekonisia. Ratnasari, Ririn Tri dan Mastuti H. Aksa. 2011. Manajemen Pemasaran Jasa. Bogor: Ghalia Indonesia.Sekaran, Uma. 2006. Metodologi Penelitian Untuk Bisnis. Jakarta: Salemba Empat.Tetuko, M. Ichsanudin Ary.2010. Studi Eksplorasi Faktor-Faktor yang Mempengaruhi Pembelian Mobil Bekas Minggu Lapangan TVRI Yogyakarta. Skripsi Tidak Diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis universitas Airlangga.Ujianto dan Abdurrachman. 2004. ”Analisis Faktor-Faktor yang Menimbulkan Kecenderungan Minat Beli”. Jurnal Manajemen dan Kewirausahaan, Vol6 No. 1, pp. 33-53.William M. Pride dan O.C. Ferrel, 1995. Pemasaran: Teori dan Praktek Sehari-hari. Jilid 1 terjemahan oleh Daniel Wirajaya. Jakarta: Erlangga. Zeithaml. 2000. Service Marketing. New Jersey: Mc Graw Hill.http://www.bi.go.id/web/id/Perbankan/P erbankan+Syariah (diakses tanggal 19 September 2013).